Fusobacterium nucleatum T18 Aggregates Human Mononuclear Cells and Inhibits Their PHA‐Stimulated Proliferation - Haake, Susan Kinder; Lindemann, Robert A. (Journal of periodontology (1970), 1997)
In previous studies Fusobacterium nucleatum has been shown to induce either stimulatory or inhibitory effects on human mononuclear cells. We examined the interaction of human mononuclear cells with human and cynomolgus monkey strains of F. nucleatum. Peripheral blood mononuclear cells (PBMCs) isolated from normal donors were aggregated in the presence of cells of F. nucleatum but not control bacteria. The aggregation of PBMCs and F. nucleatum T18 was inhibited by either L‐arginine, L‐lysine, or pretreatment of the bacterial cells with heat, but was unaffected by the presence of sugars or normal human serum. Strain T18 aggregated purified T‐cells and monocytes at approximately equal concentrations. When F. nucleatum T18 was incubated with PHA‐stimulated PBMCs, DNA synthesis in the PBMCs was significantly inhibited and detection of IL‐2Rα on the PBMCs was reduced. These studies indicate that F. nucleatum aggregates PBMCs, and that this interaction is associated with both an inhibition of PBMC proliferation and a decrease in IL‐2 receptor expression. The ability of F. nucleatum to inhibit mononuclear cell proliferation may be significant in the pathogenesis of periodontal diseases. J Periodontol 1997;68:39–44.